Factors Associated with Student-Perceived Research Quality: Evidence from Categorical Analysis at MAN Insan Cendekia East Lombok - Iqbal, Muhammad; Irfan, Ahmad Zainul; Muzakkir, Muzakkir; Muslim, Ahmad; Zulfakar, Zulfakar; Mursyid, Hidayat Joni; Maliki, Imam Maksum Al (IJBLE Scientific Publications Community Inc., 2026)
This study examines factors associated with student-perceived research quality among senior high school students at MAN Insan Cendekia Lombok Timur, Indonesia. Research quality was measured through a 10-item self-perception instrument demonstrating excellent psychometric properties with high internal consistency (Cronbach’s alpha = .863) and adequate item-total correlations (.381-.706). Using convenience sampling, 67 students participated in the study. Data were collected through Google Forms and analyzed using descriptive statistics and chi-square analysis with Monte Carlo simulation. Results indicated that students’ perceived research quality was predominantly in the moderate category (47.8%), with mean score of 77.34 (SD = 10.75). Chi-square analyses revealed no statistically significant associations between perceived research quality categories and any of the eleven student characteristics examined, including gender (chi-square = 5.699, p = .058), grade level (chi-square = 2.371, p = .306), age, monthly allowance, subject preferences, school status, school type, and academic specialization. These non-significant findings are interpreted through the lens of social cognitive theory and research skill development frameworks, suggesting that research literacy as an acquired competency through structured learning may transcend demographic and academic boundaries when educational environments provide equitable learning opportunities. Practical recommendations for enhancing research literacy programs in secondary education are discussed.